Efektifitas Penerapan Desain Pembelajaran IPS dalam Pembelajaran Daring - Adisel, Adisel; Khasanah, Ummi; Putra, Andesta; As, Lucy Andrekiy; Wulandari, Wulandari; Supriyadi, Tetap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the effectiveness of the application of social studies learning design in online learning. This study uses a descriptive method, namely the method of researching the status of a group of people, an object, a set of conditions, a system of thought or a class of events in the present. This data analysis was obtained from various sources using various data collection techniques (triangulation). The results of the study explain that online learning is effectively carried out at SMPN 5 Bengkulu City because, every student has a mobile phone with a good internet connection, making online learning applicable. in social studies subjects, students are enthusiastic about participating in learning activities well. This is because teachers use various media on the internet to support teaching and learning activities. online learning received a positive response from parents of students in suppressing breaking the chain of the spread of the covid-19 virus. In conclusion, online learning is effectively implemented in SMPN 5 Bengkulu City. Keywords: Learning Design, Online, Effectiveness,